Mechanical thrombectomy using the new Tigertriever in acute ischemic stroke patients – A Swiss prospective multicenter study. Issue 5 (October 2020) - Gruber, Philipp; Diepers, Michael; von Hessling, Alexander; Weber, Johannes; Kahles, Timo; Anon, Javier; Berberat, Jatta; Nedeltchev, Krassen; Liebeskind, David S; Remonda, Luca
Purpose: Tigertriever is a novel operator-adjustable clot retriever designed to enhance the operator's options to control the interaction of retriever and clot. The aim of this study was to assess the feasibility, safety and efficacy of the Tigertriever device system. Methods: Prospective multi-center registry study at three comprehensive stroke centers in Switzerland from 2017 to 2019 of patients with acute ischemic stroke (AIS) and large vessel occlusion (LVO) using Tigertriever as a first-line device. Results: 30 AIS patients (median age 72.5 years (IQR 64–79), 50% women) with a median NIHSS on admission of 11 (IQR 6-13) and a median ASPECT score of 9 (IQR 7–10) were treated with the new Tigertriever and included in this study. The first-pass effect was 24% (n = 7). A good recanalization (eTICI 2 b/2c/3) was achieved in 94% of the cases. Median mRS at 90 days was 1 (IQR 1–2). Conclusion: This study demonstrated feasibility, safety and effectiveness of the Tigertriever in AIS patients with LVO with a high reperfusion rate.